The Effect of Administration of Leilem Leaf Extract (Clerodendrum Minahassae) on the Histopathological Features of the Liver in Wistar Rats (Rattus Norvegicus) Induced with Cap Tikus Alcoholic Beverage - Andrea Abelia Hans; Nur Anindhita Kurniawaty; Maria Kristianti Sambuaga (CV. Publikasi Indonesia, 2026)
Excessive alcohol consumption, including traditional alcoholic beverages such as Cap Tikus (alcohol content ±45%) from North Sulawesi, can induce liver damage characterized by steatosis, inflammation, and necrosis. Leilem leaf (Clerodendrum minahassae) extract, rich in phenolic and flavonoid compounds, has potential hepatoprotective effects due to its antioxidant properties. Purpose: To evaluate the effect of Leilem leaf extract on the histopathological features of the liver in Wistar rats (Rattus norvegicus) induced by Cap Tikus alcoholic beverage. This experimental study used a post-test-only control group design with 24 male Wistar rats divided into four groups: normal control, negative control (Cap Tikus 2.16 mL/day), treatment I (Leilem extract 150 mg/kgBW + Cap Tikus), and treatment II (Leilem extract 300 mg/kgBW + Cap Tikus). Treatments were administered orally for 14 days. Liver tissue was processed for histopathological examination using hematoxylin-eosin staining and observed under a light microscope. The negative control group showed significant steatosis and inflammatory cell infiltration. The treatment groups exhibited reduced steatosis and inflammation, along with increased hepatocyte regeneration. The higher dose (300 mg/kgBW) demonstrated greater hepatoprotective effects and more prominent regeneration compared to the lower dose (150 mg/kgBW). No necrosis or fibrosis was observed in any group. Leilem leaf extract exerts a hepatoprotective effect by suppressing inflammatory responses and enhancing hepatocyte regeneration in Wistar rats induced with Cap Tikus. The highest protective efficacy was observed with Leilem leaf extract at 300 mg/kgBW.